Outcome of one-visit and multiple-visit root canal treatment for cracked tooth with pulpitis: a meta analysis - Wang, Wen; Wang, Peng-Lai; Xie, Ni-Na; Wu, Cui; Liu, Zong-Xiang (Shanghai kou qiang yi xue, 2017)
To compare the treatment effect between one-visit and multiple-visit endodontic treatment for cracked tooth with pulpitis. The literatures published before 2016-06-01 regarding to one-visit and multiple-visit root canal treatment for cracked tooth with pulpitis were searched through MEDLINE, CNKI, VIP, Wanfang Database et al. Then the included studies were chosen according to the inclusion criteria. Collection of features, quality evaluation and analysis of treatment effect, follow-up results (half year/1 year) and postoperative pain of the included studies were analyzed using Stata/SE12.1 software. A total of 24 Chinese literatures were included and no eligible foreign literatures were found. There were 3065 cases including 1608 with one-visit endodontic treatment and 1457 with multiple-visit endodontic treatment. Meta analysis showed that the effective rate (96.90%) and follow-up success rate (94.90%,94.60%) of one-visit endodontic treatment were significantly higher than multiple-visit one (84.00%,81.40%,8